The Good News Bible at 50(ish) Translation, Localization, and Alterity - Towner, Philip H. 1953- (2018)
This article will explore the Good News Bible (GNB) as an example of a translation designed to “localize” the source text—in this case, by virtue of its strategy to produce a translation in contemporary language. In this approach, designed to enhance the reader’s chance of making meaning, there are gains and losses. On one level, greater accessibility to the text for a wider audience may seem to be achieved, while at another level, access to the otherness/alterity in the source text (intertextuality, wordplay, etc.) is closed off. Several examples will illustrate some of these gains and losses in GNB.
Keywords: Good News Bible; Alterity; localization